Pemberdayaan Masyarakat dalam Pengembangan Desa Wisata Catur - Nirmalasari, Ni Luh Putu Intan (Tulisan Ilmiah Pariwisata (TULIP), 2023)
This study examines the community empowerment strategy in the development of the Catur Tourism Village. This study aims to determine the form of community participation and empowerment, the supporting and inhibiting factors for the development of Tourism Villages and to formulate strategies to empower the community in efforts to develop Catur Tourism Village. This study uses a qualitative descriptive approach with data collection methods through interviews, observations, questionnaires and documentation studies. The selection of informants was done through purposive sampling. The results of interviews and observations were analyzed by qualitative descriptive and the results of the IFAS and EFAS questionnaires were analyzed using the Internal External (IE) matrix, SWOT analysis using the theory of Participation and Community Based Tourism. The form of community participation in the development of the Catur Tourism Village is bottom-up, namely the participation by the community is genuine from the community itself. The community actively participates in empowerment activities in the form of training and assistance from government institutions, academia and the private sector. The main supporting factor of Catur Tourism Village is the potential of the agricultural sector while the main inhibiting factor is the division of community roles that have not been maximized in the development of Tourism Villages. The strategies formulated in the effort to empower the community include integration, market penetration, market development, product development and governance improvement as well as community consolidation efforts.